ANALYSIS OF THE COURT RULING NO. 42/PID.SUS -TPK/2023/PN-BNA REGARDING LEGAL PROTECTION AGAINST STATE LOSSES IN THE SALE OF LAND CERTIFICATES BY BPN ACEH JAYA OFFICIALS - Fatin Nabila; Nahara Eriyanti (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article aims to analyze the judge's considerations in decision No. 42/Pid.Sus-TKP/2023/PN-Bna regarding legal protection against state losses in the sale of land certificates by the Aceh Jaya BPN apparatus, based on the MABI concept. This case focuses on the actions of the Aceh Jaya BPN Apparatus, which forged signatures and traded land certificates illegally, resulting in state losses of Rp. 12,607,479,500 (twelve billion six hundred seven million four hundred seventy-nine thousand five hundred rupiah). This not only resulted in state losses but also harmed the community, which was deprived of its rights to land redistribution and the objectives of land reform. This study employs a qualitative approach, utilizing a case study method, as well as a normative juridical approach, to examine the juridical aspects of the sale of land certificates by the Aceh Jaya BPN Apparatus in the context of land redistribution activities related to land reform objectives that resulted in state losses. The results of the study indicate that the implementation of land redistribution activities for land reform objectives is contrary to the concept of mabi' because it does not meet the requirements for a valid sale and purchase agreement according to Islamic law, so the transaction is considered invalid according to Sharia. This study highlights the importance of monitoring the implementation of land redistribution for land reform objectives and enforcing integrity within the Aceh Jaya BPN apparatus to prevent the recurrence of authority abuse.